2015
DOI: 10.1299/jbse.15-00228
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of mechanical propertes of articular cartilage for biphasic finite element analyses

Abstract: The purpose of this study is to estimate material properties of articular cartilage by curve fitting method using finite element (FE) analysis. While various material tests have been conducted to predict the behavior of articular cartilage, one of the recent interests was the accurate estimation of material properties under physiological and dynamic condition. In this study, cylindrical indentation was experimentally conducted in high compressive amount and high compression rate in considering the physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…It was found that we required viscosity in the solid phase to generate the small peak of the non‐fibre model just after the definite compression. In the analysis of the synovial articular cartilage, the solid phase was represented by a simple elastic model [21]. The large sharp peak of the articular cartilage was represented by the collagen network structure.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that we required viscosity in the solid phase to generate the small peak of the non‐fibre model just after the definite compression. In the analysis of the synovial articular cartilage, the solid phase was represented by a simple elastic model [21]. The large sharp peak of the articular cartilage was represented by the collagen network structure.…”
Section: Discussionmentioning
confidence: 99%
“…The weeping [8] and boosted [9] mechanism were proposed based on the frictional mechanism of hydrogel material in the past. It is well known that the articular cartilage shows the time‐dependent compressive behaviour [10, 11], which was explained by a ‘biphasic model’ [12]. In the biphasic model, the cartilaginous tissue was modelled by the mixed composition of solid and fluid phase.…”
Section: Introductionmentioning
confidence: 99%